Delivering an outpatient pain service. Issue 7 (July 2022) - de Gray, Lorraine E; Seth, Bharti
Abstract: Chronic pain is a major cause of disability. Outpatient pain management services take a multidisciplinary approach based on a biopsychosocial framework, providing assessment and management of patients who suffer from chronic pain. The emphasis is on education and promotion of self-management. Appropriate facilities, management and cohesive working is essential to provide evidence-based effective pain management.